2012
DOI: 10.1371/journal.pone.0030343
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Effects of Superoxide Dismutase on Altered Visual Function of Retinal Ganglion Cells in db/db Mice

Abstract: BackgroundThe C57BLKS/J db/db (db/db) mouse is a widely used type 2 diabetic animal model, and this model develops early inner retinal neuronal dysfunction beginning at 24 weeks. The neural mechanisms that mediate early stage retinal dysfunction in this model are unknown. We evaluated visual response properties of retinal ganglion cells (RGCs) during the early stage of diabetic insult (8, 12, and 20 wk) in db/db mice and determined if increased oxidative stress plays a role in impaired visual functions of RGCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 51 publications
2
29
0
5
Order By: Relevance
“…This generation of superoxide by photoreceptors is not a side effect of using streptozotocin to induce diabetes, because staining for superoxide also has been found in photoreceptors of spontaneously diabetic animals (34). Because photoreceptors are the major cell type in the retina and possess more mitochondria than do other retinal cells, they are likely to be the major source of the retinal superoxide in diabetes.…”
Section: Discussionmentioning
confidence: 92%
“…This generation of superoxide by photoreceptors is not a side effect of using streptozotocin to induce diabetes, because staining for superoxide also has been found in photoreceptors of spontaneously diabetic animals (34). Because photoreceptors are the major cell type in the retina and possess more mitochondria than do other retinal cells, they are likely to be the major source of the retinal superoxide in diabetes.…”
Section: Discussionmentioning
confidence: 92%
“…Incremental threshold luminance sensitivity tests were conducted according to previously published methods. 17,23 In general, a criterion response for threshold irradiance was obtained by gradually increasing the intensity levels of the testing stimuli; a firing rate of two spikes per second above the baseline rate was set as a threshold response. If none of the test stimuli produced exactly two spikes per second, the threshold was determined by linear interpolation.…”
Section: Physiological Recording and Data Analysismentioning
confidence: 99%
“…Recent results in our laboratory have shown that altered visual function in RGCs, characterized by reduced receptive field (RF) size, elevated luminance threshold, and attenuated contrast threshold, can be reversed by in vitro application of SOD. 17 However, SOD is an enzyme, which makes it difficult to use as a therapeutic agent. Tauroursodeoxycholic acid (TUDCA), a potent inhibitor of apoptosis, acts by interfering with the upstream mitochondrial pathway that leads to cell death, inhibiting oxygen radical production, reducing endoplasmic reticulum (ER) stress, and stabilizing the unfolded protein response.…”
mentioning
confidence: 99%
“…These altered visual functions could, at least partly, be due to oxidative stress (Xiao et al, 2012a). Therefore, the db/db mouse may represent an adequate model for studies on the pathogenesis of DR.…”
Section: P0880mentioning
confidence: 99%
“…The altered visual functions of RGCs were characterized by the reduced receptive field center size, elevated luminance response, and attenuated contrast gain in 12-and 20-week db/db mice, respectively. These altered visual functions could, at least partly, be due to oxidative stress (Xiao et al, 2012a). Therefore, the db/db mouse may represent an adequate model for studies on the pathogenesis of DR.…”
mentioning
confidence: 99%